ANALISIS CASHBACK PADA AKAD PEMBAYARAN FINTECH DAN KEMANFAATAN DALAM PERSPEKTIF EKONOMI SYARIAH - Sudarma, Ade; Rahmat, Muhammad Imdadun; Casmita Pujiharto, Yaya Ruhenda (Institut Agama Islam Sahid Bogor, 2025)
The development of internet technology has driven changes in aspect of human transaction affairs, including buying and selling activities. Over time, the growth of online businesses has increased significantly, marked by the rise of e-commerce platforms or startups. Its implication is to encourage innovation in transaction methods. Financial technology (fintech) is one such innovation, with Go-Pay being a prominent example in Indonesia. Go-Pay is a cashless transaction application. Its ease of use and various promotions offered by Go-Pay have attracted consumers. One of the promotions that is often offered is cashback. Cashback refers to the return of funds from the purchase of products or payment for services using Go-Pay. This study aims to analyze the impact of cashback from Go-Pay transactions on the economy of society by employing a qualitative method supported by quantitative analysis, quantitative data was processed using a two-tailed T-test with SPSS version 26 assistance. Qualitative data analysis was done by using analytical descriptive case study approach and library research, incorporating a normative (Islamic law) perspective. Data validity was tested using source and technique triangulation, while the discussion applied the principles of ushul fiqh, specifically istidlal qiyasi (analogical reasoning). The results of this study show a significant value of 52.652, while the T-table at a significance level of 0.05 is 2.020. This indicates that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted. The conclusion is that cashback in Go-Pay transactions has an impact on both the economy of society and its benefits. However, from an Islamic law perspective, cashback still contains elements of riba, which users should avoid. Furthermore, it is recommended that Go-Pay clarify the terms of its transaction in detail and partner with Islamic banks.